(untitled) (Research, Society and Development, 2025)
High-performance athletes use various nutritional strategies aiming to maximize sports performance, often through aggressive manipulation of macronutrients, dehydration, and rapid weight cuts. Although these approaches may yield immediate results in competitions, scientific evidence indicates that their chronic use can compromise metabolic, renal, hormonal, and intestinal health, negatively affecting longevity. The relationship between nutrition, microbiota, circadian rhythm, and the athlete’s physiological response is complex and interdependent, which reinforces the need for personalized strategies. Thus, the objective of this study was to discuss the nutritional practices used in the preparation of high-performance athletes, as well as their impacts on longevity. This is a literature review that gathered and interpreted national and international scientific evidence published between 2007 and 2025, from databases such as SciELO, PubMed, MDPI, Google Scholar, The Psychological Society, and the European Journal of Sport Science. It was observed that while protocols like strategic fasting, macronutrient cycling, chrononutrition, and the Mediterranean diet showed lasting benefits, extreme weight loss methods and dietary imbalances exposed the body to inflammatory and metabolic dysfunctions. It was concluded, therefore, that the balance between performance and longevity depends on individualized nutritional planning, adapted to each athlete’s physiology and competitive demands.